Factors associated with hospital admission for COVID-19 in HIV patients. (1st November 2020) - Di Biagio, Antonio; Ricci, Elena; Calza, Leonardo; Squillace, Nicola; Menzaghi, Barbara; Rusconi, Stefano; Orofino, Giancarlo; Bargiacchi, Olivia; Molteni, Chiara; Valsecchi, Laura; Cenderello, Giovanni; Ferrara, Sergio; et al.
Abstract : N/A: This study reports on hospital admission and outcomes of 69 HIV-infected individuals who were diagnosed with SARS-CoV-2 infection between February and May 2020, in a network of Italian centres. Patients' characteristics and median days between symptoms and diagnosis were similar by hospital admission, whereas admitted patients had lower nadir CD4 + cells and current lymphocytes count. These values were also correlated to worse COVID-19 outcome. Antiretroviral drugs did not seem to be associated with disease severity.